BENIGN OVARIAN NEOPLASMS IN TEENAGE GIRLS - Yangibayev Jonibek Saparbayevich (Scholar Express Journals, 2022)
In modern life, everything is new and, unfortunately, tumor processes have begun to occur more and more often at a young age. Ovarian neoplasms in adolescent girls occur in 2 to 5% of cases, visits to a pediatric gynecologist. There are data on their diagnosis even in the antenatal period. There are separate casuistic reports of cases of ovarian tumors in infants: removal of an ovarian cyst of 102 g in a newborn 11 days old and removal of a granulosa cell tumor in a 16-week-old girl. It should be noted that tumors and tumorlike formations in the right ovary in girls occur much more often than in the left, due to its prevalence in anatomical and functional terms, which confirms the theory of genetic determination of an earlier and higher functional activity of the right ovary
Keywords: Benign tumors; ovarian cysts; adolescents; gynecology